A comparative numerical analysis and environment assessment to examine hydrothermal behavior of two serpentine heatsink with water/silver Nano fluid applying two-phase mixture model. (January 2023) - Wang, Dan; Dhahad, Hayder A.; Ali, Masood Ashraf; Almojil, Sattam Fahad; Almohana, Abdulaziz Ibrahim; Alali, Abdulrhman Fahmi; Almoalimi, Khaled Twfiq; Sharma, Kamal
Abstract: In the present study, the hydrothermal characteristics of two different a) serpentine (Conf. A), and b) double serpentine (Conf. B) heatsinks with water/silver Nano Fluid (NF) were studied. To this end, the Finite volume method was performed, and the governing equations were discretized based on the second upwind approach and solved numerically applying the Semi-Implicit Method for Pressure Linked Equations (SIMPLE) scheme. The results demonstrated that the thermal resistance ( R ) of Conf. A is lower than that of Conf. B at low Re numbers, and these two configurations have an identical R as Re increases to 2000. Also, the convective heat transfer in Conf. A is slightly higher than that in Conf. B and for Re =2000 both configurations have a same h value. Moreover, the increasing of nanoparticle concentration from 0% to 1% increases h by 12.55% and decreases the pressure drop (Δ P ) by 4.25%. In addition, the CPU mean temperature of Conf. A is 0.8% and 0.1% lower than that of Conf. B for Re s of 500 and 2000, respectively. On the other hand, Δ P in Conf. A is 74% higher than that in Conf. B. Besides, Conf. B exhibits a better temperature uniformity as compared to other configuration. The parameter of figure of merit was obtained as 1.47 to 1.52 at Re s of 500 and 2000, respectively, which showed that Conf. B provides a higher hydrothermal performance over the other configuration.The environmental impact of the designed heat sink is equal to 0.5388.